Estado e terceiro setor em parceria: avaliação da lei 13.019/14 - Soares, Renner Araújo (2018)
The purpose of this research is to evaluate the Legal Framework of the Third Sector in Brazil: Law 13,019 / 14, from the point of view of achieving the objectives intended when designing its Agenda within the scope of Civil Society. Among the purposes foreseen in the Law, which will be analyzed are: a) Impersonality in contracting Entities, transparency in partnerships, accountability: an expression of the efficiency of public spending. The joint action of the State and Civil Society can lead to advances in the formulation, execution and monitoring of public policies, since civil society has characteristics that facilitate and improve policies, bringing them closer to the population and making them more effective policies such as the capillarity that allows public policies to permeate the social fabric respecting all its peculiarities and formulating specific policies for specific groups. For it is ultimately (civil society) the target of the policies. The research brings a qualitative approach and has as procedures adopted: bibliographic review, documentary analysis and interviews. We had a discussion about the context in which the Regulatory Framework operated. The speech of the subjects involved was captured through open interviews. The Group chosen for the research is composed of representatives of the recipients of the Policy: by the Public Administration, spoke public administrator, by Civil society spoke leaders of the Entities, these lines allied to the other instruments used in the research allowed to conclude that the force of social mobilization around an issue (legal insecurity, criminalization of institutions) can put demands on the government's agenda, which in turn can be transformed into state public policies. Law 13,019 / 2014 is the result of this process.